Impact of tourism on sustainable development in BRI countries: The moderating role of institutional quality. - Huma Iftikhar (PLoS ONE, 2022)
This study investigated the influence of tourism on sustainable development while considering institutional quality as a moderating variable. Moreover, exchange rate, urbanization, household consumption, per capita income and renewable energy per capita were also essential factors in determining sustainable development. The sample consists of 64 Belt and Road Initiative (BRI) countries from 2003-2018. The outcomes of the two-step system GMM confirmed the statistically significant and positive dynamic nature of sustainable development and its relationship with tourism and other determinants at a significance level of 1% for BRI countries. Institutional quality enhanced the 4.693% sustainability path to achieve the sustainable development goals (SDGs) agenda with regionally interconnected countries at significance level of 1%. Renewable energy per-capita and income per-capita played a significant and positive role, while the exchange rate, household consumption, and urbanization negatively influenced by hurting thd path of sustainable development. The current research findings have valuable contributions to academics as it offers novel insights about the 0. 351% influence of tourism on sustainable development at significance level of 1%, and it proposes valued suggestions to policymakers concerning tourism development strategies.